Pohjoiset alueet muutoksessa : geopoliittinen näkökulma - Heininen, Lassi (Valtiotieteellinen yhdistys – Statsvetenskapliga föreningen, 2010)
In classical geopolitics the northernmost regions of the globe has been discussed as a reserve of natural resources and a space for the military. This periphery, the circumpolar North is also a homeland of Indigenous peoples with their identities. The industrialized and militarized High North of the Cold War started to thaw in the 1990s as a result of increased interrelations between peoples and civil societies, as well as region-building by nation-states. At the early-21st century there are interpretations saying that there is going on the Race for the Arctic, or that the region could descend into armed conflict due to a fight over natural resources within the continental shelf. None of these are, however, happening, although the geo-strategic importance of the High North is growing. Instead, there is a significant and multi-functional geopolitical, socio-economic and environmental change. Though, it is not yet easy to describe or analyze the occurring change, it has several indicators (of both classical and critical geopolitics), such as an importance of state sovereignty, energy security, institutionalized international cooperation and climate change. Final, on one hand, there is a growing global interest toward the region and its natural resources, and on the other, the High North plays more important role in world politics.